2022
DOI: 10.14309/ajg.0000000000001980
|View full text |Cite
|
Sign up to set email alerts
|

Functional Lumen Imaging Probe Panometry Helps Identify Clinically Relevant Esophagogastric Junction Outflow Obstruction per Chicago Classification v4.0

Abstract: INTRODUCTION: Esophagogastric junction (EGJ) outflow obstruction (EGJOO) per Chicago Classification v4.0 (CCv4.0) represents a high-resolution manometry (HRM) diagnosis with uncertain clinical significance. This study aimed to evaluate functional lumen imaging probe (FLIP) panometry among patients with EGJOO on HRM/CCv4.0 to assess clinical/manometric associations and treatment outcomes. METHODS:An observational cohort study was performed on patients who completed FLIP during endoscopy and had an HRM/CCv4.0 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
1
11
0
1
Order By: Relevance
“…Multiple studies have demonstrated that EGJ distensibility is reduced in achalasia 20–23 . Additionally, several studies have demonstrated that evaluating EGJ distensibility/opening among patients with inconclusive achalasia or manometric EGJOO can help identify patients with a “conclusive” disorder of EGJ outflow, thus utilization of FLIP in this scenario was recommended by the CCv4.0 13,24–26 . Further, FLIP metrics of EGJ‐DI and maximum EGJ diameter, as well as an associated classification of EGJ opening, outperformed the IRP on HRM to predict abnormal retention on TBE 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that EGJ distensibility is reduced in achalasia 20–23 . Additionally, several studies have demonstrated that evaluating EGJ distensibility/opening among patients with inconclusive achalasia or manometric EGJOO can help identify patients with a “conclusive” disorder of EGJ outflow, thus utilization of FLIP in this scenario was recommended by the CCv4.0 13,24–26 . Further, FLIP metrics of EGJ‐DI and maximum EGJ diameter, as well as an associated classification of EGJ opening, outperformed the IRP on HRM to predict abnormal retention on TBE 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Eine FLIP-Manometrie kann helfen, klinisch relevante Abflussbehinderungen zu erfassen [30]. Die Untersuchung wird im Zusammenhang mit einer ÖGD beim sedierten Patienten durchgeführt.…”
Section: Functional Luminal Imaging Probe (Flip)unclassified
“…Other alternatives for determining the clinical relevance of EGJOO exist. FLIP measuring distensibility of the LES appears to be an accurate tool to identify clinically relevant EGJOO, when assessed against longitudinal clinical outcomes 50 . Provocative testing during manometry using larger volumes of water (rapid drink challenge) or solid food to more closely replicate normal eating and drinking behavior can help clarify the significance of manometric EGJOO.…”
Section: Utility Of Barium Esophagography Alongside Other Esophageal ...mentioning
confidence: 99%
“…FLIP measuring distensibility of the LES appears to be an accurate tool to identify clinically relevant EGJOO, when assessed against longitudinal clinical outcomes. 50 Provocative testing during manometry using larger volumes of water (rapid drink challenge)…”
Section: (A) (B)mentioning
confidence: 99%
See 1 more Smart Citation